Cytotoxic assessment of aqueous extracts of Heliotropium keralense Sivar. & Manilal on Allium cepa root tip cells - Athira R. Mohan; Nisha Joseph (Caryologia)
Heliotropium keralense Sivar. & Manilal is an endangered medicinal plant native to the Indian state of Kerala. Cytotoxic effects of aqueous extracts of leaves, stems, and roots of H. keralense were evaluated using Allium cepa L. root tip method. Allium cepa bulbs were exposed to extracts of different parts of the plant for 24 hours. Compared to the negative control, a significant decrease in the length, root number and mitotic index of Allium cepa was observed with 5 to 25% aqueous extracts of H. keralense. Chromosomal abnormalities such as single, double, and multiple lesions in interphase, single and double lesions in prophase, diagonal metaphase, diagonal anaphase, bridged anaphase, strap-shaped nuclei, giant cells and chromosome loops are identified in positive control and treatments. The highest percentage of chromosomal aberration was observed in the (95.18±2.07%) positive control and 25% (71.76±7.46%) leaf extract. The analysis showed that the aqueous plant parts of H. keralense had antimitotic and cytotoxic effects. This study shows that Heliotropium keralense contains strong cytotoxic substances that can cause chromosomal aberrations.